2018
DOI: 10.1590/0102-311x00025018
|View full text |Cite
|
Sign up to set email alerts
|

Mulheres no mundo da ciência e da publicação científica

Abstract: Recent months have witnessed widespread mobilization of women in numerous countries and fields, with various objectives. Feminist struggles were expressed in the marches protesting the explicitly misogynous U.S. President's inauguration and Brazilian women's resistance to further curtailment of Brazil's already limited right to abortion. The movement has branched out, exposing countless cases of sexual harassment and abuse. The women strengthened each other to speak out, sharing their experiences through MeToo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
(4 reference statements)
0
3
0
5
Order By: Relevance
“…This study identified researchers who published the most about NCDs in C&SC, of which the majority were female. In Brazil, women answered for the authorship of approximately half of the publications between the years 2011 and 2015, representing an increase in relation to the period from 1996 to 2000, whose percentage was 38% 60 . However, women still have a lower proportion compared to men, in terms of receiving productivity grants from the National Council for Scientific and Technological Development (CNPq in Portuguese) 61 .…”
Section: Discussionmentioning
confidence: 99%
“…This study identified researchers who published the most about NCDs in C&SC, of which the majority were female. In Brazil, women answered for the authorship of approximately half of the publications between the years 2011 and 2015, representing an increase in relation to the period from 1996 to 2000, whose percentage was 38% 60 . However, women still have a lower proportion compared to men, in terms of receiving productivity grants from the National Council for Scientific and Technological Development (CNPq in Portuguese) 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Também é relevante considerar que embora dados publicados pela CAPES em 2020 (CAPES, 2020), revelem que 58% das atuais bolsas de pós-graduação fomentadas pelo programa, são pagas para pesquisadoras, estudos apontam que grande parte das mulheres não avança na carreira acadêmica. Nesta perspectiva, ainda se observa maior predominância masculina entre os cargos administrativos, professores do ensino superior, comitês de assessoramentos das agências de fomento ou recebimento de bolsas de produtividade em Pesquisa (CARVALHO; COELI; LIMA, 2018;FERREIRA;FERREIRA, 2022;MONTEIRO;ALTMANN, 2021).…”
Section: Introductionunclassified
“…We can say that every topic, every event, every congress, every challenge in the field of Public Health has been addressed in an editorial at some point, as well as the directions of health policy, new (and old) diseases, inequalities, and inequities. The role of women in science and publishing is a frequent topic of our three Editors-in-Chief 26 , but not new in the CSP: in the thematic issue published in 1991, the editorial said “ to conclude, we highlight that (with two honorable exceptions) all authors included here are female authors ” 27 (p. 134). Open science is also an increasingly present topic 28 , 29 , associated with the challenges for a gradually more collective scientific practice 30 .…”
mentioning
confidence: 98%